2021
DOI: 10.1101/2021.02.24.432704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permeant Fluorescent Probes Visualize the Activation of SARM1 and Uncover an Anti-neurodegenerative Drug Candidate

Abstract: SARM1 regulates axonal degeneration through its NAD-metabolizing activity and is a drug target for neurodegenerative disorders. We designed and synthesized fluorescent conjugates of styryl derivative with pyridine to serve as substrates of SARM1, which exhibited large red-shifts after conversion. With the conjugates, SARM1 activation was visualized in live cells following elevation of endogenous NMN or treatment with a cellpermeant NMN-analog. In neurons, imaging documented SARM1 activation preceded vincristin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The role of SARM1 as a driver of axon degeneration has been extensively studied in the context of traumatic brain injury, axotomy, and mitochondrial dysfunction, but mainly in B6 congenic Sarm1 -/- mice. The chemotherapeutic drug vincristine is widely reported to induce SARM1-dependent axon degeneration [14, 33, 34]. We exploited this to assess and confirm the loss of SARM1-dependent axonal degeneration in the Sarm1 em1.1Tftc , Sarm1 em1.2Tftc , and Sarm1 em1.3Tftc mice.…”
Section: Resultsmentioning
confidence: 99%
“…The role of SARM1 as a driver of axon degeneration has been extensively studied in the context of traumatic brain injury, axotomy, and mitochondrial dysfunction, but mainly in B6 congenic Sarm1 -/- mice. The chemotherapeutic drug vincristine is widely reported to induce SARM1-dependent axon degeneration [14, 33, 34]. We exploited this to assess and confirm the loss of SARM1-dependent axonal degeneration in the Sarm1 em1.1Tftc , Sarm1 em1.2Tftc , and Sarm1 em1.3Tftc mice.…”
Section: Resultsmentioning
confidence: 99%
“…Animal and cell culture data strongly implicate SARM1-dependent axon loss in some peripheral neuropathies, glaucoma, Parkinson's disease and other conditions [1,3,59] and human genetic studies support its involvement in rare axonopathies involving NMNAT2 mutation [7,8] and in ALS [5,6]. This, together with the complete rescue of axons by SARM1 removal when the pathway is very specifically activated [10,20] has led to considerable focus on inhibiting and knocking down SARM1 as a therapeutic strategy [3,28,32,60]. Many studies are focusing on blocking the NADase activity specifically but our data now suggest the importance of targeting NADPase and base exchange too.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies are focusing on blocking the NADase activity specifically but our data now suggest the importance of targeting NADPase and base exchange too. This is important because the most effective drugs will come from targeting the right enzyme activity, indeed small molecules are already known to influence different SARM1 activities in different ways [16,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense oligonucleotides that target SARM1 and lower SARM1 levels in axons by more than 50% were also shown to slow degeneration in vitro ( Gould et al, 2021 ). Furthermore, the first small molecule inhibitors of SARM1 have been discovered and are shown to slow axon degeneration in DRGs to the same level as Sarm1 −/− ( Hughes et al, 2021 ; Li et al, 2021 ). Interestingly, the Hughes et al paper indicated that the inhibitor could be added up to 3 h after injury with the same level of protection, and could even protect axons fated to degenerate through rotenone exposure and promote recovery from the latent stage of degeneration back towards healthier axons ( Hughes et al, 2021 ).…”
Section: Links To Diseases and Future Therapiesmentioning
confidence: 99%